CORPORATE SOCIAL RESPONSIBILITY: THE DISCLOSURE OF AN INCLUSIVE REGULATORY MODEL - Khokhar, Farqaleet; Asad, Ali; Naheed, Dr. Khawar; Mazhar , Fatima (The journal of contemporary issues in business and government, 2022)
Corporate Social Responsibility has great significance because due to it the corporate bodies not only consider the interest of the stakeholders but also consider the environmental, economic, and social impact of their actions. CSR has a broad spectrum and it is a “ voluntary action” that the companies or businesses take to address the issues related to “ corporate irresponsible behavior” regarding social issues including labour, environmental, abuses of human rights. However, the piece inspects CSR as the mechanism for business operations, from the manufacturing and delivery of services or products to generating and promoting the interaction with the stakeholders of the company in a way to protect and encourage moral values or ethical conduct, legal requirements, and social expectations. For this purpose, the paper discusses the relationship between CSR and corporate governance to find the convergence between both. CSR in current times is weakly promoted due to the fact that the initiatives of CSR are existing without any socio-economic developmental impact. To fill that gap this paper conducts qualitative research and the research piece is an endeavor to examine CSR regulation including prescriptive and selfregulation. The piece explores the limitation of CSR regulation and constructs a framework for enhancing the accountability mechanism in CSR practices. The paper provides a more dynamic, responsive, effective, and coherent framework called the “ inclusive regulatory model.”